2012
DOI: 10.1111/jan.12050
|View full text |Cite
|
Sign up to set email alerts
|

Capacity for care: meta‐ethnography of acute care nurses' experiences of the nurse‐patient relationship

Abstract: AimsTo synthesize evidence and knowledge from published research about nurses' experiences of nurse-patient relationships with adult patients in general, acute inpatient hospital settings.BackgroundWhile primary research on nurses' experiences has been reported, it has not been previously synthesized.DesignMeta-ethnography.Data sourcesPublished literature from Australia, Europe, and North America, written in English between January 1999–October 2009 was identified from databases: CINAHL, Medline, British Nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(86 citation statements)
references
References 45 publications
(216 reference statements)
2
81
1
2
Order By: Relevance
“…The majority of research on nurses' sense of engagement with patients is discussed in qualitative studies of nursing role/relationships (e.g., Andes & Shattell, 2006;Bridges et al, 2012;Cleary, Hunt, Horsfall, & Deacon, 2012;Shattell, Andes, & Thomas, 2008). As Cleary et al's (2012) review of 23 qualitative studies points out, nurses have developed communication styles and approaches to forge connections with patients: approaches that are quite sophisticated and fit well with the often challenging inpatient environment.…”
Section: How Do Nurses' Experience Inpatient Care Settings?mentioning
confidence: 97%
“…The majority of research on nurses' sense of engagement with patients is discussed in qualitative studies of nursing role/relationships (e.g., Andes & Shattell, 2006;Bridges et al, 2012;Cleary, Hunt, Horsfall, & Deacon, 2012;Shattell, Andes, & Thomas, 2008). As Cleary et al's (2012) review of 23 qualitative studies points out, nurses have developed communication styles and approaches to forge connections with patients: approaches that are quite sophisticated and fit well with the often challenging inpatient environment.…”
Section: How Do Nurses' Experience Inpatient Care Settings?mentioning
confidence: 97%
“…1 Nurses, through communication skills, can recognize the patient’s healthcare needs, as a meaningful communication with patients enable nurses aspire to enhance a thorough knowledge of individual patients and their personal characteristics. 2 In fact, positive nurse-patient relationship includes a wide range of behaviors in multiple domains of nursing practice and it is an essential factor in high quality nursing care. 3 Therefore, enhancing the communication role of nurses leads to their having a positive opinion of their job and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Bridges et al, concluded that supportive organizational settings influenced the emotional engagement of nurses with patients. 2 Kim et al, conducted a study to explore enabling factors for nurses in communication effectively with patients. They concluded that the manager should consider a set of clinic-based strategies for improving the nurse-patient relationship beyond the conventional communication skills.…”
Section: Introductionmentioning
confidence: 99%
“…As previously illustrated in the scholarly literature on nurse-patient interaction on breaking bad news (e.g. Arber and Gallagher, 2003;Bridges et al, 2013;Dowling, 2006;Long-Sutehall et al, 2011;Malloy et al, 2010), the nurses' self-reported approaches were viewed as very different from medical discussions which were centred on diagnostic, prognostic and supportive care discussions. The nurses often found their role was to engage in highly intimate discussions about 'where they will go' and 'what's for me after' which challenged the nurses in terms of the boundaries between personal relationships and professional advice:…”
Section: Healthmentioning
confidence: 97%